Cover Image. Issue 3 (25th March 2021) - Frew, John; Penzi, Lauren; Suarez‐Farinas, Mayte; Garcet, Sandra; Brunner, Patrick M.; Czarnowicki, Tali; Kim, Jaehwan; Bottomley, Claire; Finney, Robert; Cueto, Inna; Fuentes‐Duculan, Judilyn; Ohmatsu, Hanako; et al.
Abstract : The cover image is based on the Original Article The erythema Q‐score, an imaging biomarker for redness in skin inflammation by John Frew et al., https://doi.org/10.1111/exd.14224 .